Phylogeographic analysis of invasive Asian earthworms (Amynthas) in the northeast United States. Issue 4 (13th October 2016) - Schult, Nancy; Pittenger, Kelly; Davalos, Sam; McHugh, Damhnait
Abstract: Phylogeographic studies are useful in reconstructing the history of species invasions, and in some instances can elucidate cryptic diversity of invading taxa. This can help in predicting or managing the spread of invasive species. Among terrestrial invasive species in North America, earthworms can have profound ecological effects. We are familiar with the centuries‐old invasions of European earthworms (Lumbricidae) and their impacts on nutrient cycling in soils. More recent invasions by Asian earthworms of the family Megascolecidae are less fully understood. We used data for two mitochondrial gene fragments, cytochrome oxidase I (COI) and 16S rRNA, to examine the relationships among populations of Asian earthworms in the megascolecid genus Amynthas in the northeast United States. Recent reports have indicated that one species in particular, Amynthas agrestis, is having detrimental effects in mixed forest ecosystems, and we were interested in understanding the invasion history for this species. We were surprised to discover three divergent mitochondrial lineages of Amynthas occurring sympatrically in upstate New York. Given the gap between intra‐ and inter‐lineage sequence divergences, we propose that these three lineages represent cryptic species of Amynthas, one of which is A. agrestis . For each of the three lineages of Amynthas, we observed shared haplotypes across broad geographic distances. This may reflect common origins for populations in each lineage, either by direct routes from native ranges or through post‐introduction spread by natural dispersal or human‐mediated transport within North America. Management efforts focused on horticultural imports from Asia, commercial nurseries within the USA, and on prohibition of bait disposal may help to reduce the further invasion success of Amynthas .